Extranodal extension in oral cancer: A role for the nodal microenvironment? - Pilborough, Alice E.; Lambert, Daniel W.; Khurram, Syed A. (Journal of oral pathology & medicine, 2019)
Oral squamous cell carcinoma (OSCC) is a significant cause of morbidity and mortality worldwide and accounts for the majority of head and neck cancers. Metastasis of primary tumours, primarily to cervical lymph nodes in the neck, is associated with worsening prognosis. Furthermore, the prognosis of patients with extranodal extension of metastatic tumour from the lymph nodes into the neck tissues is particularly poor. The factors affecting this process are poorly understood, and detection is difficult pre‐surgery. Mounting evidence shows that components of the tumour microenvironment including cancer‐associated fibroblasts, vascular and lymphatic endothelial cells, the extracellular matrix and inflammatory immune cells, are important modulators of tumour behaviour in primary OSCC and other cancers. However, little is known about the lymph node microenvironment, its response to tumour presence and role in extranodal extension. In addition, there are many lymph node‐specific cell types and structures, such as fibroblast reticular cells and high endothelial venules, making the lymph node microenvironment distinct from that found at primary tumour sites, and which contribute to the nodal response to tumour presence. This review details the current knowledge regarding the lymph node tumour microenvironment in OSCC and its role in lymph node metastasis and extranodal extension and relates this to features of the primary tumour. Understanding the role that the lymph node microenvironment plays in promoting tumour development and extranodal extension may aid the identification of novel biomarkers and alternative treatment strategies to improve the prognosis of patients with advanced OSCC.